Prostate Cancer Information Available in Health-Care Provider Offices: An Analysis of Content, Readability, and Cultural Sensitivity - Choi, Seul Ki (Am J Mens Health, 2018)
Prostate cancer (PrCA) is the most common cancer affecting men in the United States, and African American men have the highest incidence among men in the United States. Little is known about the PrCA-related educational materials being provided to patients in health-care settings. Content, readability, and cultural sensitivity of materials available in providers’ practices in South Carolina were examined. A total of 44 educational materials about PrCA and associated sexual dysfunction was collected from 16 general and specialty practices. The content of the materials was coded, and cultural sensitivity was assessed using the Cultural Sensitivity Assessment Tool. Flesch Reading Ease, Flesch-Kincaid Grade Level, and the Simple Measure of Gobbledygook were used to assess readability. Communication with health-care providers (52.3%), side effects of PrCA treatment (40.9%), sexual dysfunction and its treatment (38.6%), and treatment options (34.1%) were frequently presented. All materials had acceptable cultural sensitivity scores; however, 2.3% and 15.9% of materials demonstrated unacceptable cultural sensitivity regarding format and visual messages, respectively. Readability of the materials varied. More than half of the materials were written above a high-school reading level. PrCA-related materials available in health-care practices may not meet patients’ needs regarding content, cultural sensitivity, and readability. A wide range of educational materials that address various aspects of PrCA, including treatment options and side effects, should be presented in plain language and be culturally sensitive.